Prototipe Perahu Listrik: Pengaruh Ukuran Propeller Terhadap Resistance dan Power Pada Software Maxsurf Resistance - Ahmad Ilham Ramadhani; Dwi Dharma Arta Kusuma; Andie Murtono; Ahmad Tubagus Tsani Risqi Aji (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
The boat model as a prototype of an electric boat has been successfully modeled and simulated using Maxsurf software. The research aims to determine the resistance and power values of the boat when operating using the Holtrop method. The Pakura boat was modeled using a Maxsurf modeler and simulated using Maxsurf resistance. Based on the modeling results, it shows that the boat model corresponds to the main dimensions in real conditions. The Pakura boat model has a displacement of 320.5 kg, amidship and immersed draft of 0.25 m, and a wetted area of 2.94 m2. The resistance and power are calculated using the resistance and power holotrop methods. Based on the simulation results, we obtained a prototype model of an electric boat that can operate on a certain propeller size. The maximum speed of the electric boat prototype with a 7-inch propeller is 4.31 kn. At 1500 rpm, the boat receives an HR of 92.71 N and requires a power of 205.57 W. On an 8-inch propeller that is 4.82 kN. At 1500 rpm, the boat receives an HR of 121.83 N and requires a power of 302.08 W. The size of the propeller affects the resistance value and power of the boat. The resistance value of the boat and operating power requirements increase along with changes in rpm on the electric engine. This can be used as a reference in determining the propulsion components for an electric boat prototype.